Ethical Considerations in Determining Standard of Prevention Packages for HIV Prevention Trials: Examining PrEP. Issue 2 (31st May 2013) - Haire, Bridget; Folayan, Morenike Oluwatoyin; Hankins, Catherine; Sugarman, Jeremy; McCormack, Sheena; Ramjee, Gita; Warren, Mitchell
Abstract The successful demonstration that antiretroviral (ARV) drugs can be used in diverse ways to reduce HIV acquisition or transmission risks – either taken as pre‐exposure prophylaxis (PrEP) by those who are uninfected or as early treatment for prevention (T4P) by those living with HIV – expands the armamentarium of existing HIV prevention tools. These findings have implications for the design of future HIV prevention research trials. With the advent of multiple effective HIV prevention tools, discussions about the ethics and the feasibility of future HIV prevention trial designs have intensified. This article outlines arguments concerning the inclusion of newly established ARV‐based HIV prevention interventions as standard of prevention in HIV prevention trials from multiple perspectives. Ultimately, there is a clear need to incorporate stakeholders in a robust discussion to determine the appropriate trial design for each study population.